Translation-a technique for improving L2 in advanced learners - Moscoso Amador, María de Lourdes
This research examines the role of translation along with the aids of Contrastive Analysis to determine whether these techniques are valuable tools to improve students? advanced level of English. The study took place in Universidad del Azuay, with the collaboration of 15 participants from International Studies. It was found that translation is natural and almost inevitable to students in bilingual classrooms, therefore it is only coherent to follow this expected drive and take advantage of it by making students exploit the benefits of this positive learning resource that can have still more to present if it is combined with the advantages that Contrastive Analysis has to offer. On the whole, this technique has the advantage of raising students? awareness and straightens the weak structures advanced learners still have to overcome. The present research should be taken as a beginning in the area of translation as a technique for improving second language. Further research should be encouraged.